2023
DOI: 10.1513/annalsats.202201-029oc
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and Turnover Intention in Critical Care Professionals During the COVID-19 Pandemic in Japan: A Cross-sectional Survey

Abstract: Rationale The prevalence of burnout among critical care professionals during the coronavirus disease (COVID-19) pandemic varies in different countries. Objectives To investigate the prevalence of burnout and turnover intention in Japanese critical care professionals in March 2021. Methods This cross-sectional study used a web-based survey of Japanese critical care professionals working in 15 intensive care units in 15 prefectures. Burnout was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 55 publications
(68 reference statements)
0
12
0
Order By: Relevance
“…Both organizational and individual interventions bring value to managing work-related stress, improving well-being at work, and alleviating fatigue and moral distress, thereby allowing to decrease the prevalence of burnout in ICU professionals [ 57 ]. High resilience capacities and strong perceived support from the hospital have also been shown to be associated with lower odds of burnout and turnover intention while the presence of burnout increased turnover intention [ 58 ]. To promote a policy of reduction of psychosocial risks in the ICU environment, some scientific societies have initiated a call to action to enhance the critical care community’s interest in reducing the prevalence of BOS and promoting a healthy work environment in the ICU [ 7 ].…”
Section: Limitationsmentioning
confidence: 99%
“…Both organizational and individual interventions bring value to managing work-related stress, improving well-being at work, and alleviating fatigue and moral distress, thereby allowing to decrease the prevalence of burnout in ICU professionals [ 57 ]. High resilience capacities and strong perceived support from the hospital have also been shown to be associated with lower odds of burnout and turnover intention while the presence of burnout increased turnover intention [ 58 ]. To promote a policy of reduction of psychosocial risks in the ICU environment, some scientific societies have initiated a call to action to enhance the critical care community’s interest in reducing the prevalence of BOS and promoting a healthy work environment in the ICU [ 7 ].…”
Section: Limitationsmentioning
confidence: 99%
“…Perpetrating potentially morally injurious events (PMIEs) and passively witnessing PMIEs during COVID-19 impacted turnover intention for nurses [ 97 ]. Two studies showed that increased scores of psychological resilience were associated with a lower score of professional turnover intention [ 93 , 119 ]. In contrast, two other studies showed that resilience was negatively correlated with the intention to resign [ 106 , 120 ].…”
Section: Resultsmentioning
confidence: 99%
“…The chronological age of the nurses was divided into two categories: 20 s, and 30 years or older. Years of nursing experience has been reported as a variable that influences turnover intention [ 27 , 35 ], with turnover intention in the COVID-19 pandemic higher for nurses with fewer years of experience [ 24 , 36 ]. The present study investigated the distribution of nurses’ years of experience during the COVID-19 pandemic.…”
Section: Methodsmentioning
confidence: 99%
“…A survey of hospitals accepting COVID-19 patients in Japan also showed that the increase in COVID-19 patients had a negative effect on nurses’ mental health and intention to resign [ 26 ]. Japanese critical care professionals have suggested that intensive care unit nurses may experience increased burnout and turnover intention because they routinely bear the responsibility for healthcare during pandemics and are exposed to infection through their close contact with patients [ 27 ]. It is therefore important to identify factors that affect turnover intentions, focusing on the workload of frontline nurses in hospitals receiving COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%